Pengembangan Blok Fungsi Kendali PI-Fuzi pada IEC 61499 - Lebukan, Dirga Eka Putra; Wardana, Awang Noor Indra; Effendy, Nazrul (Jurnal Teknik Elektro, 2019)
Automation system in the form of automatic control is needed in one or several operating units in the process industry. Several control system algorithms have been widely implemented in the process industry, one of them is PI (Proportional and Integral) controller. This PI controller has a simple structure, but the adaptive ability of the controller is still not better for the controlled process. Therefore, the development of PI controller is needed to have a better adaptive ability to the process, in order to produce the responses that are also better and more robust. This research develops PI controller by adding the Fuzzy controller algorithm or also known as PI-Fuzzy controller. The PI-Fuzzy controller in this study is applied to the IEC 61499 Programmable Logic Controller (PLC) standard and to see its performance, the PI-Fuzzy controller based on IEC 61499 is tested and validated on an industrial scale process, namely coal mill. The test was carried out for three hours in real-time on the 4DIAC-IDE software, then the response results were compared with the response results of the PI controller. The PI-Fuzzy controller function block based on IEC 61499 made in this study showed good performance in controlling industrial-scale processes. This is demonstrated in testing and validation using a coal mill, with able to achieve the working range of each parameter. The mean value of coal flow parameter is 13.584 kg/s, coal mass accumulation is 2,196 kg, coal output temperature is 83.296 0C, coal moisture is 0.021, and coal fineness is 75.338 %.